DRAGON YAM BEAN VELVA BERBASIS BUAH NAGA MERAH DAN BENGKUANG SEBAGAI ALTERNATIF SELINGAN SUMBER SERAT INULIN DAN ANTOSIANIN - ,Nia Fatimah Nurjanah; Roro Nur Fauziyah; Dadang Rosmana (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2020)
Not infectious disease (PTM) have become a health problem for every country. One of the main contributors who use PTM is food control, by consuming foods that contain inulin (bengkuang tubers) and anthocyanins (dragon fruit). Intermittent food products consisting of velva become more effective because in one product already has a lot of special nutritional content of inulin and anthocyanin fibers. The design of this study was experimental with a completely randomized design (CRD). The research method uses hedonic tests, spectrophotometry for anthocyanin levels, and literature tests for inulin fiber levels. This study involved 30 panelists who were apparently students of the Nutrition Department of the Poltekkes Bandung. This product formulation consists of three dragons and bengkuang, which is counterpart 1 (30%: 70%), counterpart 2 (70%: 30%), and counterpart 3 (50%: 50%). The hedonic test results showed that the level of preference consisted of counterpart 2 and the Kruskal-Wallis test results showed differences between the aspects of color, taste, and aroma with a value of p <α and also none in the design of the texture with p> α. The level of anthocyanin product serving is 6.04 mg and can fulfill 81% of the anthocyanin requirement by consuming two serving sizes. While the level of inulin per serving amounted to 2.1 g and can meet the needs of inulin at least a day from 350% snack.